KAJIAN IMPLEMENTASI PSAK NO. 46 MENGENAI PAJAK PENGHASILAN DALAM PERSEPKTIF PENGUKURAN, PENGAKUAN, PENYAJIAN DAN PENGUNGKAPAN ATAS FINANCIAL STATEMENT PT. CHANDRA ASRI PETROCHEMICAL RENTANG WAKTU 2020-2022 - Isnayani, Dea Nur (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
One of the biggest sources of state revenue comes from taxes. Tax is an obligation that must be paid by citizens every year. One source of state revenue in the tax sector comes from income taxes. PSAK 46 is the basis for the accounting treatment of income tax which regulates the measurement, recognition, presentation and disclosure and liability of tax consequences in future periods. PT. Chandra Asri Petrochemical Tbk is the most popular petrochemical producing company in Indonesia which in 2022 received an award for the best tax payment category by KPP Big Two Taxpayers. The research uses descriptive techniques with a case study style that provides an explanation of the implementation of PSAK No. 46 in the financial statements obtained by accessing it on the website of the Indonesia Stock Exchange (IDX), namely https://www.idx.co.id/ and the company's official website. The results of the study show that the financial statements of PT Chandra Asri Petrachemical have been prepared and carried out by the four perspectives in the Financial Accounting Standards (SAK) with the provisions of PSAK No. 46 and there is no change in the four aspects of SAK every year.